CO2 and Water Vapor Emissions are the “Tail” of Global Warming and Anthropogenic Heat Emissions are what Matters – Demonstration Through ChatGPT - Pirot, Florent; Mezhennaya, Maria (European Journal of Applied Sciences, 2025)
The climate change debate often revolves around the role of CO2 emissions as a key driver of global warming. However, recent studies, including those referenced in International Journal of Physics 7-4-3, suggest that anthropogenic heat losses and volcanic activities might play a significant role in climate dynamics, without needing to attribute warming directly to CO2. This perspective challenges the mainstream CO2-centric view by emphasizing the potential for volcanic tephras, aerosols, and waste heat from industrial activities to influence atmospheric temperatures. Volcanic eruptions, especially large events like the Samalas VEI-7 eruption, release substantial amounts of material that can both cool and warm the climate through various radiative processes. In addition, anthropogenic heat loss, generated by human industrial activity, is a potent source of atmospheric energy that contributes to climate warming, particularly in industrial regions. The study argues that CO2 emissions are simply an indirect consequence of these activities, and have no warming effect per se. This view offers a nuanced understanding of climate dynamics, focusing on volcanic and anthropogenic interactions while questioning the traditional CO2-driven models. The implications of these findings urge a reassessment of how we model and address climate change in modern science.